A aplicação das ferramentas do Google no jornalismo: um estudo das redações da fronteira oeste do RS - (:unkn) unknown (Universidade Federal do Pampa, 2016)
The changes in the labor market have a direct impact on the production routines of newsrooms. Information and communication technologies have multiplied as news production possibilities and have demanded a new professional profile. One of the companies that stand out the most in the provision of resources for editorial staff is Google, which has greatly facilitated the work of journalists. For this reason, the objective of this work is to identify the tips of the tools made available by Google that are most used by journalistic production teams in the western border of Rio Grande do Sul. It was sought to understand how users use the tools to Optimize your data collection process when producing a message, add data to your productions, or even search for information to keep you up to date. The research was carried out with a questionnaire application of communication companies of the western border of Rio Grande do Sul, in the cities of Itaqui, São Borja and Uruguaiana.
Keywords: Jornalismo; Redação de textos jornalísticos; Google; Rio Grande do Sul; Fronteiras; Journalism; Writing journalistic texts; CNPQ::CIENCIAS SOCIAIS APLICADAS